2008 International Wireless Communications and Mobile Computing Conference 2008
DOI: 10.1109/iwcmc.2008.151
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Adjacent Channel Interference in Multi-Radio Systems using IEEE 802.11

Abstract: A promising approach for improving the capacity of Wireless Mesh Networks is by making use of multiple non-overlapping RF channels. Multi-channel protocols have the advantage that several devices can transmit in parallel within a collision domain on distinct channels. When using IEEE 802.11b/g/a most protocol designers assume 3 and 12 non-overlapping channels, respectively. However, this simplified assumption does not hold. We present results from measurements that show that the number of available non-interfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 12 publications
0
29
0
Order By: Relevance
“…Based on this assumption measurements were only conducted with Tx values between 10 dBm to 15 dBm. In comparison to other previously published work, such as [9] and [10], the following results show every combination of Tx and DR with T and RSSI, respectively. As explained in detail in Section II-A for every calculated sample meanμ, CI is also be provided.…”
Section: Multi-radio Experimentsmentioning
confidence: 50%
See 1 more Smart Citation
“…Based on this assumption measurements were only conducted with Tx values between 10 dBm to 15 dBm. In comparison to other previously published work, such as [9] and [10], the following results show every combination of Tx and DR with T and RSSI, respectively. As explained in detail in Section II-A for every calculated sample meanμ, CI is also be provided.…”
Section: Multi-radio Experimentsmentioning
confidence: 50%
“…Additionally, their assumption has already been disproved by many researchers, such as [7] [9] [10], ACI issues must be taken into account when conducting multi-radio measurements with IEEE 802.11a hardware. One of the most important pieces of work in relation to this issue are the results of Nachtigall et al [9]. They demonstrated that the number of available non-interfering channels depends on both the antenna separation and the Physical Layer (PHY) modulation.…”
Section: B Adjacent Channel Interferencementioning
confidence: 99%
“…However, for the 40 MHz link, the impact is less than when it overlaps with 20 MHz links. This is probably due to the mechanism CSMA/CA which in this case has less spurious carrier sensing and less frames are corrupted ( [2,3]). …”
Section: Is It Worth Using 40 Mhz Channels?mentioning
confidence: 99%
“…Many works (e.g., [1][2][3][4][5][6][7][8][9]) study different characteristics of WiFi in practice, but still more practical tests and a larger set of experiments are needed. For example, most of the works are focused only on the 2.4 MHz band or only study a reduced set of aspects of the 5GHz band.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, separating APs into different channels may decrease cochannel interference. However, in nonoverlapping channels, an 802.11-based multiradio device suffers board crosstalk, radiation leakage, and adjacent channel interference [5], [32], [33]. These problems are hardware dependent [5] and can be alleviated by utilizing hardware and radio frequency (RF) techniques such as shielding, bandpass filters, and antenna separation by distances or orientations [32], [33].…”
Section: A Ieee 80211 and Ieee 80211smentioning
confidence: 99%